Main factors influencing landed homeowners from installing rainwater harvesting system - Low, Ian Ming Hans (2022)
The research aims to identify some of the factors that will influencing the landed homeowners from installing Rainwater Harvesting Systems, and then evaluate which are the most impactful factors that will influence the landed homeowners. A total of 5 factors were identified: Cost Factor, Awareness Factor, Incentives Factor, Water Demand Factor, and Government Policies Factor. To evaluate the impact of these 5 factors, a survey is done in Greater Kuala Lumpur, and the survey received 102 responses. The collected data was proven reliable with a Reliability Analysis using the SPSS Analysis Tool, and then further analysed using Descriptive Analysis and the Relative Importance Index (RII) methods. It is found that the Water Demand Factor would be the most influencing factor to the landed homeowners in Greater Kuala Lumpur. At the end of the study suggested the limitations of the research, and the improvements that can be made to the research.